Simple Bookkeeping Training at the Rembun Village Farmer Group, Dampit, Kabupaten Malang - Yogatama, Ahmad Nizar; Hanif, Rifki; Sidi, Agus Purnomo; Anjaningrum, Widiya Dewi; Cahyaningtyas, Fadilla; Dura, Justita (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The training activity entitled "Training on Simple Bookkeeping Preparation in Rembun Village Farmer Group" is an effort to provide basic understanding to Rembun Village farmer groups in managing their agricultural finances and bookkeeping more efficiently. Method: The training focuses on applying simple bookkeeping methods, which aim to help farmers record financial transactions, understand financial statements, and improve their financial management. Practical Applications: During the training, participants were taught the basic concepts of bookkeeping, cash management, recording agricultural transactions, using simple spreadsheets, and preparing financial statements. They are also introduced to mobile applications that can facilitate their bookkeeping process. The result of this training is expected to be an increase in the ability of farmer groups to manage their finances, optimize the use of resources, and produce more accurate financial reports. Conclusion: With this new understanding, Rembun Village farmer groups are expected to improve their operational efficiency and achieve sustainability in their agricultural business. This training is the first step in empowering the Rembun Village farmer group, with the hope that they can continue to improve their financial management and achieve greater success in agriculture.